PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS DISCOVERY LEARNING UNTUK MELATIH KETERAMPILAN BERPIKIR KRITIS SISWA SMP - Ni Kadek Devi Marlia Putri; I Nyoman Suardana; Kompyang Selamet (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Critical thinking skills are one of the essential 21st-century competencies that urgently need to be trained at the junior high school level. However, reality in the field shows that this ability is still relatively low due to the limited visualization of learning media and the dominance of teacher-centered lecture methods. This study aims to describe the characteristics, as well as to analyze the validity, practicality, and readability of interactive learning media based on discovery learning on the topic of nutrients and the human digestive system for junior high school students. This type of research is Research and Development (R&D) using the ADDIE development model, which is limited to the Development stage. The trial subjects involved 2 content and media expert lecturers, 5 science teachers, and 15 eighth-grade students at SMP Negeri 3 Banjar. Data collection used a questionnaire method with a Likert scale instrument analyzed descriptively through qualitative and quantitative approaches. Content validity was calculated using Gregory's cross-tabulation formula. The results showed that: (1) the media was developed using the Genially platform in the form of a responsive URL by integrating 6 syntaxes of discovery learning and Ennis's critical thinking indicators, equipped with a Virtual Lab for food tests, scientific animation videos, and interactive quizzes; (2) the content validity obtained a score of 1.00 (very high validity category) and the media validity obtained a score of 0.93 (very high validity category); (3) the practicality test by science teachers obtained an average score of 3.64 (very practical category); and (4) the readability test by students obtained an average score of 3.67 (very readable category). Based on these overall results, the developed interactive learning media is declared valid, practical, and highly readable, making it suitable for use as an interactive and contextual digital learning resource to improve junior high school students' critical thinking skills. ABSTRAK Keterampilan berpikir kritis merupakan salah satu kompetensi abad ke-21 yang mendesak untuk dilatih pada jenjang pendidikan menengah. Realitas di lapangan menunjukkan kemampuan ini masih tergolong rendah karena keterbatasan visualisasi media dan dominasi metode ceramah. Penelitian ini bertujuan untuk mendeskripsikan karakteristik, menganalisis validitas, kepraktisan, dan keterbacaan media pembelajaran interaktif berbasis discovery learning pada materi zat makanan dan sistem pencernaan untuk siswa SMP. Jenis penelitian ini adalah penelitian pengembangan (Research and Development) menggunakan model ADDIE yang dibatasi hingga tahap pengembangan (Development). Subjek uji coba melibatkan 2 orang dosen ahli materi dan media, 5 orang guru IPA, serta 15 orang siswa kelas VIII di SMP Negeri 3 Banjar. Pengumpulan data menggunakan metode kuesioner dengan instrumen angket skala Likert yang dianalisis secara deskriptif kualitatif dan kuantitatif. Uji validitas isi dihitung menggunakan rumus kesepakatan Gregory. Hasil penelitian menunjukkan bahwa: (1) media dikembangkan menggunakan platform Genially berbentuk URL dengan mengintegrasikan 6 sintaks discovery learning dan indikator berpikir kritis Ennis, dilengkapi fitur Virtual Lab uji makanan, video ilmiah, dan kuis interaktif; (2) validitas isi materi memperoleh skor 1,00 (sangat tinggi) dan validitas media memperoleh skor 0,93 (sangat tinggi); (3) uji kepraktisan oleh guru memperoleh skor rata-rata 3,64 (sangat praktis); dan (4) uji keterbacaan oleh siswa memperoleh skor rata-rata 3,67 (sangat terbaca). Berdasarkan hasil tersebut, media pembelajaran interaktif yang dikembangkan dinyatakan layak, sangat praktis, dan sangat terbaca sebagai bahan ajar digital terintegrasi untuk melatih keterampilan berpikir kritis siswa secara mandiri.